Effect of strain rate on microstructure evolution of a nickel-based superalloy during hot deformation - Zhang, Hongbin; Zhang, Kaifeng; Zhou, Haiping; Lu, Zhen; Zhao, Changhong; Yang, Xiaoli (Materials in engineering, 2015)
[Display omitted] •The DRX process was accelerated at high strain rates due to high stored energy and adiabatic heating.•The grains with GOS value less than 2° were considered as DRX grains for the studied alloy.•Majority of Σ3 boundaries were formed in the DRX process by growth accidents.•There was a sluggish evolution of Σ3 boundaries at an intermediate strain rate of 1s−1. The hot deformation behavior of a nickel-based superalloy was investigated by means of isothermal compression tests in the strain rate range of 0.001–10s−1 at 1110°C. Transmission electron microscope (TEM) and electron backscatter diffraction (EBSD) technique were used to study the effect of strain rate on the microstructure evolution of the alloy during hot deformation. The results revealed that the dynamic recrystallization (DRX) process was stimulated at high strain rates (ε̇⩾5s-1) due to the high dislocation density and adiabatic temperature rise. Meanwhile, high nucleation of DRX and low grain growth led to the fine DRX grains. In the strain rate rage of 0.001–1s−1, the volume fraction of DRX grains increased with the decreasing strain rate, and the grain growth gradually governed the DRX process. Moreover, the strain rate has an important effect on DDRX and CDRX during hot deformation. On the other hand, particular attention was also paid to the evolution of twin boundaries during hot deformation. It was found that there was a lower fraction of Σ3 boundaries at the intermediate strain rate of 1s−1, while the fractions of Σ3 boundaries were much higher at both the lower strain rates (ε̇⩽0.1s-1) and higher strain rates (ε̇⩾5s-1).